“Factors influencing learner`s motivation in learning English language in the students of Fifth semester at language career of Universidad Nacional de Chimborazo”, in the city of Riobamba, Chimborazo province, in the academic year 2015-2016” - Quitio Pilataxi, Mayra Maribel (2016)
This research work analyzes the factors influencing motivation in the students of fifth semester at the Language Career at Universidad Nacional de Chimborazo, in Riobamba, Chimborazo, during the academic year 2015-2016, since they do not acquire a significant learning of the English language as a second language. The problem studied was that the motivation factors influence in the students´ interest to learn English. This research aims to analyze, describe, identify and of an exploratory level, which allowed us to collect data through the survey technique whose instrument was the questionnaire, it considered of 10 closed questions, which was applied to the students in order to know the motivation factors that influence in the students in English Language Learning. The qualitative method applied was the ethnographic; it allowed us to carry out the study in a direct and natural context. The result obtained was the identifications of the motivation factors for the second language. It is concluded that the motivation factors really influence in the learning of the English Language.